ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN AKADEMIK MAHASISWA STAIN BATUSANGKAR - KURNIA, LELY (Sainstek : Jurnal Sains dan Teknologi, 2011)
This research was focused on studying the factors influencing the students? learning outcome, especially for the students of science Department of STAIN Batusangkar. The dependent variable was GPA that reflects the students? learning outcome. The GPA data were categorized into ?fail? (GPA<2.75), and ?successful? (GPA?2.75) that analyzed by using logistic regression and loglinear model. The respondents of this research were 339 students from Math, Physic and Biology Departmen who registered in 2008 - 2010 academic year. The logistic regression analysis showed that there were 3 factors that influence the students? learning outcome significantly; their village, UN mean score and major in high school. The data analysis indicated that the students graduated from Islamic High School had a bigger chance to succes than students from Vocational School. UN mean score also can reflect the academic ability of the student significantly and the approriate major in high school (Science Studies) gave contribution to the students? comprehension. By using loglinear analysis, it is gotten that association effect/ interaction between dependent variable and other variables as controller. The significant variable interaction was the second interaction between the school and the major chosen, while the third interaction has between UN mean score, major, and the school. Keywords: students learning outcome, logistic regression, probability, loglinear models